Influence of ejection fraction on biomarker expression and response to spironolactone in people at risk of heart failure: findings from the HOMAGE trial. (5th March 2022) - Ferreira, João Pedro; Verdonschot, Job A.J.; Girerd, Nicolas; Bozec, Erwan; Pellicori, Pierpaolo; Collier, Timothy; Mariottoni, Beatrice; Cosmi, Franco; Hazebroek, Mark; Cuthbert, Joe; Petutschnigg, Johannes; Heymans, Stephane; et al.
Abstract : Aims: Left ventricular ejection fraction (LVEF) can provide haemodynamic information and may influence the response to spironolactone and other heart failure (HF) therapies. We aimed to study patient characteristics and circulating protein associations with LVEF, and whether LVEF influenced the response to spironolactone. Methods and results: HOMAGE enrolled patients aged >60 years at high risk of developing HF with a LVEF ≥45%. Overall, 527 patients were randomized to either spironolactone or standard of care for ≈9 months, and 276 circulating proteins were measured using Olink® technology. A total of 364 patients had available LVEF determined by the Simpson's biplane method. The respective LVEF tertiles were: tertile 1: <60% ( n = 122), tertile 2: 60%–65% ( n = 121), and tertile 3: >65% ( n = 121). Patients with a LVEF >65% had smaller left ventricular chamber size and volumes, and lower natriuretic peptide levels. Compared to patients with a LVEF <60%, those with LVEF >65% had higher levels of circulating c‐c motif chemokine ligand‐23 and interleukin‐8, and lower levels of tissue plasminogen activator, brain natriuretic peptide (BNP), S100 calcium binding protein A12, and collagen type I alpha 1 chain (COL1A1). Spironolactone significantly reduced the circulating levels of BNP and COL1A1 without significant treatment‐by‐LVEF heterogeneity: BNP change β = −0.36 log2 and COL1A1 change β = −0.16 log2 ( p < 0.0001 for both; interaction p > 0.1 for both). Spironolactone increased LVEF from baseline to month 9 by 1.1% ( p = 0.007). Conclusion: Patients with higher LVEF had higher circulating levels of chemokines and inflammatory markers and lower levels of stretch, injury, and fibrosis markers. Spironolactone reduced the circulating levels of natriuretic peptides and type 1 collagen, and increased LVEF.